Geometric phase effects in the ultracold D + HD ⃗ D + HD and D + HD ↔ H + D2 reactions. (15th December 2016) - Kendrick, B K; Hazra, Jisha; Balakrishnan, N
Abstract: The results of accurate quantum reactive scattering calculations for the D + HD( v = 4, j = 0) → D + HD( v ′, j ′ ), D + HD( v = 4, j = 0) → H + D2 ( v ′, j ′ ) and H + D2 ( v = 4, j = 0) → D + HD( v ′, j ′ ) reactions are presented for collision energies between 1 μ K and 100 K . The ab initio BKMP2 PES for the ground electronic state of H3 is used and all values of total angular momentum between J = 0 − 4 are included. The general vector potential approach is used to include the geometric phase. The rotationally resolved, vibrationally resolved, and total reaction rate coefficients are reported as a function of collision energy. Rotationally resolved differential cross sections are also reported as a function of collision energy and scattering angle. Large geometric phase effects appear in the ultracold reaction rate coefficients which result in a significant enhancement or suppression of the rate coefficient (up to 3 orders of magnitude) relative to calculations which ignore the geometric phase. The results are interpreted using a new quantum interference mechanism which is unique to ultracold collisions. Significant effects of the geometric phase also appear in the rotationally resolved differential cross sections which lead to a very different oscillatory structure in both energy and scattering angle. Several shape resonances occur in the 1– 10 K energy range and the geometric phase is shown to significantly alter the predicted resonance spectrum. The geometric phase effects and ultracold rate coefficients depend sensitively on the nuclear spin. Thus, experimentalists may be able to control the reaction by the selection of a particular nuclear spin state.